ANALISIS KELEMBAGAAN DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA - Yuniati Setiyaningsih; Susilo Utomo; Priyatno Harsasto (Journal of Politic and Government Studies, 2017)
Dewan Pewakilan Daerah (DPD) RI is a region represetative body that members of delgated of region and class in MPR were originally. The third amandment of UUD 1945 conclude that DPD was as members of MPR and parlement di second chambers. But constitution give legislative power just for DPR. DPD that a balances power for DPR have weak authority and make it just as a co-legislator of DPR..By this research, the writer want to explain how the probability of relationship  changed between two chamber (DPD and DPR) that capable of carrying the strengthening of DPD in political representation in Indonesia. The method used is the type of case study research.Base on interviews and study documentation, the relationship between DPD and DPR that capable of strengthen DPD is there are a parallel of  authotity, complementary and not for mutual competitions.  The way to make it happen is by the DPD strengthened by fiveth amandment of UUD 1945, change the recruitment system, and close down of MPR RI. With based on Structuration Theory by Anthony Giddens, showed that  structur constraint that constitutions and personal capability of DPD RI members,  can also provide an opportunity for strengthening of DPD. The opportunities are supported by the political dynamics of the external DPD such as PDI-P of the ruling party then and now, DPR and distruth of  political representatives, local communities and pathner PEMDA at the center of goverment,   to offer recruitment and space the existence of the party cadres, chairs led DPR / MPR's party winning the election , In addition factors that support are already  draf for fiveth amandment and there is a decision of MPR No.. 4 / MPR / 2014 about MPR’s  2009-2014 recommendations. Keyword: DPD, Strengthening, Structur